A RP-HPLC METHOD FOR SIMULTANEOUS DETERMINATION OF HALOPERIDOL AND TRIHEXYPHENIDYL HYDROCHLORIDE IN TABLET DOSAGE FORM - DAMMALAPATI, SRIKANTHA; RUDRA RAJU, RAMESH RAJU (Asian Journal of Pharmaceutical and Clinical Research, 2014)
A simple, fast and precise reversed phase-high performance liquid chromatographic (RP-HPLC) method is proposed for simultaneous determination of the binary mixture of haloperidol and tri- hexyphenidyl hydrochloride in pharmaceutical formulations. This method uses a mobile phase consisting of methanol:acetonitrile:water (50:40:10 v/v/v), Zodiac C18 column in isocratic mode, detection wavelength of 221 nm and a flow rate of 1.2 ml/minutes. The measured retention times for haloperidol and trihexyphenidyl hydrochloride are 6.12Â±0.02 and 8.06Â±0.02 minutes, respectively. The resolution of the two chromatographic peaks is 8.23. The validation of the method showed good linearity in the range 5-50 Î¼g/ml for haloperidol and in the range 2-20 Î¼g/ml for trihexyphenidyl hydrochloride. Further, satisfactory results are also established in terms of mean percent- age recovery (99.01-99.77% for haloperidol and 99.08-100.33% for trihexyphenidyl hydrochloride), intra-day and inter-day precision (<2%) and robustness. The advantages of this method are good resolution with sharper peaks and sufficient precision. This could be used for the determination of the above drugs in dosage forms in combination or individually and in bulk.